A Latent Class Analysis of the Antisocial Attitudes Domain of the Youth Level of Service/Case Management Inventory - Costaris, Matt (Criminal justice and behavior, 2022)
Antisocial attitudes are a strong predictor of reoffending and frequently incorporated into risk assessment tools, including the Youth Level of Service/Case Management Inventory (YLS/CMI). However, YLS/CMI Attitudes/Orientation domain items appear to cover different issues—antisocial attitudes and willingness to engage in treatment—which have different implications for case management and service provision. Latent Class Analysis of data from 798 Canadian youth probationers identified four classes based on item endorsement on the Attitudes/Orientation domain: High Overall Attitude Needs (19%), Predominantly Antisocial Attitude Items (20%), Predominantly Lack of Service Engagement (9%), and Low Overall Attitude Needs (52%). Class differences were found on index offense, criminogenic needs, and recidivism, with the High Overall Attitude Needs class presenting as most “negative,” followed by Predominantly Antisocial Attitude Items, Predominantly Lack of Service Engagement, and Low Overall. Understanding attitudes based on this class conceptualization can assist probation officers in targeting services more effectively to justice-involved youth.